Analysis of Ca2+-mediated sperm motility to evaluate the functional normality of the sperm-specific Ca2+ channel, CatSper - Hwang, Jae Yeon (Frontiers in Cell and Developmental Biology, 2024)
Ca 2+ is a key secondary messenger that modulates sperm motility by tuning flagellar movement in various species. The sperm-specific Ca 2+ channel, CatSper, is a primary Ca 2+ gate that is essential for male fertility in mammals. CatSper-mediated Ca 2+ signaling enables sperm to develop hyperactivated motility and fertilize the eggs in the female tract. Therefore, altered CatSper function compromises the entry of Ca 2+ into sperm followed by impairing hyperactivation and male fertility. However, methods to evaluate the function of the CatSper channel are limited to patch clamping and functional imaging using Ca 2+ dye. Previous studies have revealed that various parameters for sperm motility are highly correlated with intracellular Ca 2+ levels in mouse. Here, I cover a step-by-step protocol to analyze Ca 2+ -mediated sperm motility change by using computer-assisted semen analysis, CASA, to evaluate the functional normality of the CatSper channel in sperm. This approach analyzes the sperm motility parameters during intracellular Ca 2+ chelation followed by in vitro capacitation to recover intracellular Ca 2+ via the activated CatSper channel. Thus, this Ca 2+ -handling method is handy and could be broadly applied in reproductive biology labs as well as clinics that have CASA equipment to examine the functional normality of the CatSper channel.